Test suite design for code generation tools - Stürmer, Ingo; Conrad, Mirko (18th IEEE International Conference on Automated Software Engineering, 2003. Proceedings, 2003)
In model-based development, executable specifications (models) are used for the design of the software to be developed. New techniques allow the automatic generation of compact code directly from the model via so-called code generators. However, at present, code generators do not possess the same quality characteristics as C or ADA compilers which have been proven in use. The use of test suites, which make it possible to check compilers systematically, is also a promising approach for code generators. This paper describes the design of such a test suite for code generators, and introduces a new testing approach for code generator transformations.